Peningkatan Perekonomian Masyarakat Melalui Pengembangan Wilayah Wisata (Studi Kasus Kelurahan Alun-Alun Contong Kota Surabaya) - Fauzatul Laily Nisa fauzatul; Nur Hanif nur; Marseto marseto (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Tourism development is expected to have an impact on the community's economy. This is because tourism is a non-oil and gas sector that contributes greatly to the economy. Alun-Alun Contong Village, Surabaya City has tourism potential that can be used as a spear to improve the community's economy. However, this opportunity has received less attention. The purpose of this community service is to introduce tourism potential in Contong Alun-Alun Village which can be used as tourist attractions for the government, private sector and the general public. After conducting a study, in the Alun-Alun area, many historical relics were found as capital resources to increase tourism development. As a result of this community service, a tourism awareness group (Pokdarwis) was formed, a plan for the development of tourism facilities and infrastructure, and the introduction of tourism potential. The existence of tourism potential will have an economic impact on the surrounding community. This study uses a qualitative method with a descriptive approach. Data collection techniques by observation, interviews and documentation. After doing the research, the strategies that can be carried out by Alun-Alun Contong Village for tourism development are community empowerment, training on tourism, and improving facilities and infrastructure. The efforts of Alun-Alun Contong Village also face several inhibiting factors such as the lack of human resources and public awareness of the existing potential and capital to develop tourism